2021
DOI: 10.1038/s41598-021-02015-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and compositional changes in the gut microbiota of wild and captive vertebrates: a meta-analysis

Abstract: The gut microbiota is recognised as an essential asset for the normal functioning of animal biology. When wild animals are moved into captivity, the modified environmental pressures are expected to rewire the gut microbiota, yet whether this transition follows similar patterns across vertebrates is still unresolved due to the absence of systematic multi-species analyses. We performed a meta-analysis of gut microbiota profiles of 322 captive and 322 wild specimens from 24 vertebrate species. Our analyses yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…However, anthropogenic influences can erode the host-lineage specificity of gut microbiota through a process of humanization, in which hosts acquire microbiota constituents found in humans ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ). For example, although the specific effects of captivity on microbiota differ among mammalian species (e.g., Houtz et al, 2021 , Alberdi et al, 2021 ; reviewed in Diaz and Reese, 2021 ), several studies have shown that captive mammals harbor gut microbiota constituents abundant in humans but missing from wild-living conspecific populations ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ), suggesting transmission from humans. If host species and microbiota have adapted to one another, disruption and replacement of native microbiota may have adverse consequences for host phenotypes and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…However, anthropogenic influences can erode the host-lineage specificity of gut microbiota through a process of humanization, in which hosts acquire microbiota constituents found in humans ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ). For example, although the specific effects of captivity on microbiota differ among mammalian species (e.g., Houtz et al, 2021 , Alberdi et al, 2021 ; reviewed in Diaz and Reese, 2021 ), several studies have shown that captive mammals harbor gut microbiota constituents abundant in humans but missing from wild-living conspecific populations ( Clayton et al, 2016 ; Houtz et al, 2021 ; Trevelline and Moeller, 2022 ), suggesting transmission from humans. If host species and microbiota have adapted to one another, disruption and replacement of native microbiota may have adverse consequences for host phenotypes and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the hypothesis that transfer of animals from their natural habitat to captivity can induce rapid and extensive changes to the gut microbiota composition and thereby affect other aspects of animal welfare. However, many unanswered questions relating to the effect of habitat changes on gut microbiota in animals still exist, as a meta-analysis study has also shown that the differences between wild and captive microbiomes are heterogeneously distributed and cannot simply be generalized across species (Alberdi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In studies investigating a large number of animal species, it is possible to compare microbiota between groups or habitats (Ley et al, 2008 ; McKenzie et al, 2017 ; O'Donnell et al, 2017 ; Youngblut et al, 2019 ; Alberdi et al, 2021 ). A frequent observation has been a reduced microbial diversity in captive individuals compared to their wild counterparts in some animal species (Kohl et al, 2014 ), while others have observed species-specific differences (McKenzie et al, 2017 ; Alberdi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4). It is expected that recipient communities would not match donors identically, as the Mus host physiology reshapes donor communities 30 , and our donor communities were collected from individuals in the wild, and thus our design does not account for the well-documented effects of captivity on the microbiome 31 . The comparatively lower colonization efficiency among Herb-CONV mice may have been driven by the low content of indigestible plant fibers that are primarily fermented by microbes.…”
Section: Introductionmentioning
confidence: 99%